2019
DOI: 10.1111/pirs.12382
|View full text |Cite
|
Sign up to set email alerts
|

Commuting time, public exposure and victimization: Evidence from Brazilian metropolitan regions

Abstract: Routine activities theory establishes that the greater the exposure to public spaces with weak guardianship the higher the probability of being a victim of urban violence. Using a unique dataset for the year 2009 that includes all Brazilian metropolitan regions, we provide evidence for the causal effect of a long commute time on the chance of being a victim of violence in these urban centres. The set of evidence was obtained by applying propensity score matching techniques to create counterfactuals and is robu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
2
3
0
Order By: Relevance
“…A similar pattern of attenuation is found for the effects associated with urbanization gains, which are expected to have a larger spatial scope, suggesting the presence of strong urban congestion costs in Brazil. In any event, this result appears to be in line with the difficulties of urban mobility of Brazilian cities (see, e.g., Silveira Neto et al, 2015; Silveira Neto & Moura, 2019) and the consequent difficulties in spatial matching with occupations by workers pointed out by Haddad and Barufi (2017). Importantly, this evidence brings an enlightening qualification to recent evidence of agglomeration gains obtained by Chauvin et al (2017) and Silva and Azzoni (2021) for Brazilian urban centers: rather than homogeneous application to all urban space, as assumed by these works, such gains appear extremely localized.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…A similar pattern of attenuation is found for the effects associated with urbanization gains, which are expected to have a larger spatial scope, suggesting the presence of strong urban congestion costs in Brazil. In any event, this result appears to be in line with the difficulties of urban mobility of Brazilian cities (see, e.g., Silveira Neto et al, 2015; Silveira Neto & Moura, 2019) and the consequent difficulties in spatial matching with occupations by workers pointed out by Haddad and Barufi (2017). Importantly, this evidence brings an enlightening qualification to recent evidence of agglomeration gains obtained by Chauvin et al (2017) and Silva and Azzoni (2021) for Brazilian urban centers: rather than homogeneous application to all urban space, as assumed by these works, such gains appear extremely localized.…”
Section: Resultssupporting
confidence: 70%
“…A similar pattern of attenuation is found for the effects associated with urbanization gains, which are expected to have a larger spatial scope, suggesting the presence of strong urban congestion costs in Brazil. In any event, this result appears to be in line with the difficulties of urban mobility of Brazilian cities (see, e.g., Silveira Neto et al, 2015;Silveira Neto & Moura, 2019) and the consequent difficulties in spatial matching with occupations by workers pointed out by Haddad and Barufi (2017).…”
Section: Baseline Resultssupporting
confidence: 66%
“…Silveira Neto et al (2015) confirmed the shorter commuting time for women in the SPMR and highlighted the role of marriage and household responsibility to understand gender commuting time differences. Silveira Neto and Moura (2019) also showed that longer commuting times positively affect the chance of being a victim of urban violence in Brazilian metropolitan regions, with this effect being stronger for women than men.…”
Section: Introductionmentioning
confidence: 88%
“…Further, the literature documents gender differentials in commuting time in the São Paulo metropolitan region, suggesting that marital status exerts a strong influence on the commuting time of working women (Silveira Neto et al, 2015). In turn, greater exposure to public spaces with weak guardianship is related to a higher probability of being a victim of urban violence in Brazilian metropolitan regions (Silveira Neto and Moura, 2019). Regarding the relationship between the built environment and commuting, Gainza and Livert (2013) find for the city of Santiago de Chile that the use of public transit reduces the environmental impact of commuting, but the modal choice depends not only on the effectiveness of the transit system but also on the characteristics of the urban form and other socio-economic determinants.…”
Section: Related Literaturementioning
confidence: 99%
“…The relationship between transport mode choice and perceived security is especially important for commuting, a complex phenomenon (Guell et al, 2012) associated with lower subjective well-being (Dickerson et al, 2014; Roberts et al, 2011), and greater stress (Gottholmseder et al, 2009; Novaco and Gonzalez, 2009; Stutzer and Frey, 2008; Wener et al, 2003). In the case of Latin America, longer commutes are associated with a higher probability of experiencing depression (Wang et al, 2019), and an increase in the probability of being a victim of violence (Silveira Neto and Moura, 2019). Thus, the relationship of commuting to perceived security deserves further attention.…”
Section: Introductionmentioning
confidence: 99%